2014
DOI: 10.1158/1078-0432.ccr-13-2642
|View full text |Cite
|
Sign up to set email alerts
|

Hypermethylation of theGABRE∼miR-452∼miR-224Promoter in Prostate Cancer Predicts Biochemical Recurrence after Radical Prostatectomy

Abstract: Purpose: Available tools for prostate cancer diagnosis and prognosis are suboptimal and novel biomarkers are urgently needed. Here, we investigated the regulation and biomarker potential of the GABRE$miR-452$miR-224 genomic locus.Experimental Design: GABRE/miR-452/miR-224 transcriptional expression was quantified in 80 nonmalignant and 281 prostate cancer tissue samples. GABRE$miR-452$miR-224 promoter methylation was determined by methylation-specific qPCR (MethyLight) in 35 nonmalignant, 293 prostate cancer [… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

18
96
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 89 publications
(114 citation statements)
references
References 48 publications
18
96
0
Order By: Relevance
“…In addition, the expression levels of miR-452 were lower in all examined breast cancer cell lines than in the human breast epithelial cell line MCF-10A. Similar results have been reported for non-small cell lung cancer (24), prostate cancer (25) and glioma (26). These findings suggest that the low expression of miR-452 may be a common event in human cancer, and may be associated with metastasis of breast cancer.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In addition, the expression levels of miR-452 were lower in all examined breast cancer cell lines than in the human breast epithelial cell line MCF-10A. Similar results have been reported for non-small cell lung cancer (24), prostate cancer (25) and glioma (26). These findings suggest that the low expression of miR-452 may be a common event in human cancer, and may be associated with metastasis of breast cancer.…”
Section: Discussionsupporting
confidence: 83%
“…miR-452 has been reported to be abnormally expressed in numerous types of human cancer (24)(25)(26). However, no specific studies have been performed to reveal the expression and biological roles underlying miR-452 in breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…However, miR-452 expression in malignant tumors is controversial. Although miR-452 was also found to be downregulated in a variety of malignancies such as prostate cancer (18), breast cancer (19) and glioma (20), this miRNA was highly expressed in esophageal cancer (21) and urothelial carcinoma (22), as well as in hepatocellular carcinoma (23). Our previous study has documented that miR-452 expression was down-regulated in human NSCLC tissues compared with the corresponding adjacent tissues (11).…”
Section: Discussionmentioning
confidence: 96%
“…These stemness regulators reduced stem-like traits tumorigenesis (20). Furthermore, functional studies suggested that miR-452 inhibited proliferation, migration and invasion of prostate cancer cells via regulation of pathways of cell cycle and cellular adhesion and motility, and finally associated biochemical recurrence (18). In our previous study, we found that higher expression of miR-452 could inhibit NSCLC cell invasion and metastasis capability by modulating BMI1 expression, suggesting that miR-452 plays an important role in development of NSCLC (11).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that miR-452-5p expressions in different neoplasms are distinct, which is upregulated in urinary tract epithelial tumors, esophageal cancer, and liver cancer, [18][19][20] but downregulated in breast cancer, prostate cancer, and glioma. [21][22][23] Currently, there have been only a few reports regarding the relationship between miR-452-5p and lung cancer. The clinical significance and possible molecular function (MF) of miR-452-5p in NSCLC was reported by Zhang et al 24 and He et al 25,26 However, clinical samples in their research were restricted by region and quantity, and the complicated mechanism of miR-452-5p in LUAD remained unclear.…”
Section: Introductionmentioning
confidence: 99%